A fuzzy-PID composite controller for core power control of liquid molten salt reactor. (May 2020) - Zeng, Wenjie; Jiang, Qingfeng; Xie, Jinsen; Yu, Tao
Highlights: Based on a two-region nonlinear model of MSBR core, a linear model of MSBR core is designed. To study MSBR core power control, the PID controller and the fuzzy controller are respectively used. To draw on the merits of PID controller and fuzzy controller, a fuzzy-PID composite controller is designed. Abstract: As the fluidity of molten salt fuel in liquid molten salt reactor, it is difficult to build an accurate mathematical model for the core power control system. In order to solve the problem, a fuzzy-PID composite control method is presented. First, a nonlinear model of liquid molten salt reactor core is established by two-region model. Then, the nonlinear model is linearized by linearization method of small perturbation with the single-input single-output model. In order to draw on the merits of fuzzy controller and PID controller, a fuzzy-PID composite controller is designed. The composite controller can control a system by automatically switching between fuzzy control and PID control according to the range of error. The results of the simulation show that the fuzzy-PID composite controller combines the merits of the two control methods, and its synthetic qualities are better than the common PID controller and the basic fuzzy controller.